Short-circuit constrained distribution network reconfiguration considering closed-loop operation - Macedo, Leonardo H. [UNESP]; Home-Ortiz, Juan Manuel [UNESP]; Vargas, Renzo; Mantovani, José Roberto Sanches [UNESP]; Romero, Rubén [UNESP]; Catalão, João P.S. (Elsevier, 2022)
This paper presents a novel scenario-based stochastic mixed-integer second-order cone programming model to solve the problem of optimal reconfiguration of distribution systems with renewable energy sources considering short-circuit constraints. The proposed formulation minimizes technical losses by modifying the statuses of sectionalizing and tie switches, allowing the operation of distribution networks with radial and closed-loop topologies. Since the formation of loops could impact fault current levels, short-circuit constraints are considered in the problem formulation. Numerical experiments are carried out using an 84-node system and the results demonstrate the effectiveness of the proposed formulation to reduce technical losses notably when a closed-loop operation is allowed. Additionally, it is verified that short-circuit constraints prevent the adoption of network configurations with high short-circuit values.
Keywords: Closed-loop operation; Distribution network reconfiguration; Renewable energy sources; Short-circuit; Stochastic programming